2007
DOI: 10.1177/000348940711600903
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Heavy Chain Composition and Fiber Size of the Cricopharyngeus Muscle in Patients with Achalasia and Normal Subjects

Abstract: Patients with CA had relatively fewer type I fibers, although the difference was not statistically significant. The MHC isoform composition and fiber size were not different between CA patients and normal subjects. This is the first report to characterize the CPM in patients with CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The type I myofibres provide the tonic force for maintaining closure of the upper oesophageal sphincter (Davis et al . ). Interestingly in murine cricopharyngeal muscle, we observed an inner layer of myofibres expressing neonatal MHC, instead of type I MHC.…”
Section: Discussionmentioning
confidence: 97%
“…The type I myofibres provide the tonic force for maintaining closure of the upper oesophageal sphincter (Davis et al . ). Interestingly in murine cricopharyngeal muscle, we observed an inner layer of myofibres expressing neonatal MHC, instead of type I MHC.…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers have investigated the histology of cricopharyngeal dysfunction, and one paper has suggested that there are histological patterns in specimens taken from the cricopharyngeus muscle that can predict responses to botulinum toxin 30 . However, there are no clear trends in this study and in other papers, and the sample sizes reported are far too small to draw any conclusions 2 …”
Section: Discussionmentioning
confidence: 67%
“…In humans the cricopharyngeal muscle has been shown to be made up of 72 % type I myosin heavy chain fibres. It was, however, found that there is no statistical difference in the isoform and type of myosin heavy chain fibres between humans with CA and normal patients 2 .…”
Section: Introductionmentioning
confidence: 92%
“…However, the presence of the foreign material that is very slowly removed via macrophages will worsen any aspiration pneumonia present. It has been reported in humans that barium sulphate can cause a non-fibrotic form of pneumoconiosis 2,6 .…”
Section: Radiologymentioning
confidence: 99%
See 1 more Smart Citation